GE_GERICHTE A/1507/2003 vom 10. November 2004 - GE Cour de justice (2004)
; AI(ASSURANCE) ; FIBROMYALGIE ; COMORBIDITÉ ; DEGRÉ DE L'INVALIDITÉ ; MALADIE ; INVALIDITÉ(INFIRMITÉ) ; INCAPACITÉ DE TRAVAIL